Arbekacin: another novel agent for treating infections due to methicillin-resistant Staphylococcus aureus and multidrug-resistant Gram-negative pathogens - Matsumoto T (Dove Medical Press, 2014)
Tetsuya Matsumoto Department of Microbiology, Tokyo Medical University, Tokyo, Japan Abstract: Arbekacin sulfate (ABK), an aminoglycoside antibiotic, was discovered in 1972 and was derived from dibekacin to stabilize many common aminoglycoside modifying enzymes. ABK shows broad antimicrobial activities against not only Gram-positive bacteria including methicillin-resistant Staphylococcus aureus (MRSA) but also Gram-negative bacteria such as Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae. ABK has been approved as an injectable formulation in Japan since 1990, under the trade name Habekacin, for the treatment of patients with pneumonia and sepsis caused by MRSA. The drug has been used in more than 250,000 patients, and its clinical benefit and safety have been proven over two decades. ABK currently shows promise for the application for the treatment of multidrug-resistant Gram-negative bacterial infections such as multidrug-resistant strains of P. aeruginosa and Acinetobacter baumannii because of its synergistic effect in combination with beta-lactams. Keywords: synergistic effect, Habekacin, MRSA, multidrug-resistant Gram-negative bacteria